Sex-ratio adjustment when relatives interact: a test of constraints on adaptation. - West, SA; Shuker, D; Sheldon, B (2005)
Studies of sex allocation offer excellent opportunities for examining the constraints and limits on adaptation. A major topic of debate within this field concerns the extent to which the ability of individuals to adaptively manipulate their offspring sex ratio is determined by constraints such as the method of sex determination. We address this problem by comparing the extent of sex-ratio adjustment across taxa with different methods of sex determination, under the common selective scenario of interactions between relatives. These interactions comprise the following: local resource competition (LRC), local mate competition (LMC), and local resource enhancement (LRE). We found that: (1) species with supposedly constraining methods of sex determination showed consistent sex-ratio adjustment in the predicted direction; (2) vertebrates with chromosomal sex determination (CSD) showed less adjustment then haplodiploid invertebrates; (3) invertebrates with possibly constraining sex-determination mechanisms (CSD and pseudo-arrhenotoky) did not show less adjustment then haplodiploid invertebrates; (4) greater sex-ratio adjustment was seen in response to LRC and LMC than LRE; (5) greater sex-ratio adjustment was seen in response to interactions between relatives (LRC, LMC, and LRE) compared to responses to other environmental factors. Our results also illustrate the problem that sex-determination mechanism and selective pressure are confounded across taxa because vertebrates with CSD are influenced primarily by LRE whereas invertebrates are influenced by LRC and LMC. Overall, our analyses suggest that sex-allocation theory needs to consider simultaneously the influence of variable selection pressures and variable constraints when applying general theory to specific cases.